Predation risk shapes the use of conflicting personal risk and social safety information in guppies. (23rd August 2021) - Feyten, Laurence E A; Crane, Adam L; Ramnarine, Indar W; Brown, Grant E
Abstract: When faced with uncertainty, animals can benefit from using multiple sources of information in order to make an optimal decision. However, information sources (e.g., social and personal cues) may conflict, while also varying in acquisition cost and reliability. Here, we assessed behavioral decisions of Trinidadian guppies ( Poecilia reticulata ), in situ, when presented with conflicting social and personal information about predation risk. We positioned foraging arenas within high- and low-predation streams, where guppies were exposed to a personal cue in the form of conspecific alarm cues (a known indicator of risk), a novel cue, or a control. At the same time, a conspecific shoal (a social safety cue) was either present or absent. When social safety was absent, guppies in both populations showed typical avoidance responses towards alarm cues, and high-predation guppies showed their typical avoidance of novel cues (i.e., neophobia). However, the presence of social safety cues was persuasive, overriding the neophobia of high-predation guppies and emboldening low-predation guppies to ignore alarm cues. Our experiment is one of the first to empirically assess the use of safety and risk cues in prey and suggests a threshold level of ambient risk which dictates the use of conflicting social and personal information. Abstract : Social animals can supplement information gathered from the physical environment with information from peers. When these sources convey conflicting information, individuals must prioritize one cue when making a behavioural decision. Here, guppies from populations with either high or low predation risk relied on social safety cues when uncertain about a potentially risky chemical cue. However, only the low-risk guppies prioritized the social safety cues over a chemical cue that was known to be dangerous.